Combination therapy of chitosan, gynostemma, and motherwort alleviates the progression of experimental rat chronic renal failure by inhibiting STAT1 activation - Bai, Wenxia (Oncotarget, 2018)
This study aimed to investigate the effect of single and combination therapy using chitosan (K), gynostemma (J), and motherwort (Y) on an experimental rat model of chronic renal failure (CRF) induced by adenine and the underlying mechanisms. CRF rats were treated with individual or combinational therapy with two or three of these agents. Biochemical indicators showed that the levels of blood urea nitrogen, creatinine and uric acid decreased and the levels of albumin and hemoglobin increased by single or combination therapy of these drugs. Drug treatment also decreased oxidative stress damage of renal tissues in CRF rats. Histopathological lesions were attenuated in each drug treatment group by various degrees. Additionally, drug treatment affected the expression of extracellular matrix (ECM) proteins including plasminogen activator inhibitor 1, collagen I, matrix metalloprotease-1, and tissue inhibitor of metalloproteinases 1. In particular, the combination therapy of K, J, and Y was superior to the respective monotherapy, which supported the prescription of KJY combination. We further studied the inhibitory effect of KJY on LPS-induced inflammation in RAW264.7 macrophages. The results showed that KJY inhibited LPS-induced secretion of inflammatory cytokines (Interferon-gamma, Interleukin-1 Beta, chemokine (C-X-C motif) ligand 10, cyclooxygenase-2 and Tumor necrosis factor-α in RAW264.7 macrophages. Combination therapy of KJY suppressed the protein expression of Cyclooxygenase-2 and inducible nitric oxide synthase in vivo and in vitro. Further study indicated that KJY inhibited STAT1 activation by down regulating p-STAT1 to exert anti-inflammatory effect and improve renal function in rats with chronic renal failure.